Sistem Informasi Penerimaan Mahasiswa Baru Dengan Framework Laravel - Samsul Budiarto; Teddy Hidayat; Sandi Nugroho (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Admission of new students is one of the processes that exist in every educational institution such as universities which is useful for screening each selected prospective student. In general, this process is carried out through the registration process, file selection, and announcements. The implementation of new student admissions is carried out on a scheduled and routine basis every year. The purpose of this research is to create a system that can be used to assist the new student admissions department of the University of Nurtanio Bandung in recording prospective new students, the selection process, until the announcement of the results of the new student selection. It is hoped that this will facilitate the process of accepting new students. The proposed system is web-based so that it can be accessed by users anywhere and anytime as long as it is connected to an internet connection. In the implementation of this system using the Laravel framework which has a little execution time so it has a fast loading process